Diferentes caras del ‘sacrum’ en el discurso literario rioplatense - Maksymilian Drozdowicz (Studia Linguistica, 2024)
This paper is an overview of many researchers’ opinions on the presence of a religious element in La Plata’s literature. The perspective of the article is definitely diachronic, critical and analytical. According to the conclusions of the literature researchers, there is a strict relationship between theological thinking and the current social and cultural issues and the ideological layer of particular literary works. A novelty in our study is that what is seemingly absent from the religious subject area can function as a visible sign of theological thinking in La Plata’s work. Even anticlerical attitudes may be indicating a religious background of their authors. Almost no literary work of La Plata may be considered as devoid of theological motifs or inspiration.